Droplet wetting and evaporation on hydrophilic and hydrophobic surfaces - Phonkrit, Boonchuaysream (Nanyang Technological University, 2020)
This report investigates the behavior of droplet wetting and evaporation on hydrophilic and hydrophobic substrates. In particular, water droplets wetting and evaporation dynamics on smooth, cavity patterned and pillar patterned PMMA films were investigated. Aluminum oxide and titanium oxide coatings were also used to change the substrate wettability. Patterned substrates have micropillars that decrease the wettability of the surface, making the substrate more hydrophobic, resulting in larger intrinsic contact angles. The droplets show circular initial wetting shapes on the smooth substrate while octagonal wetting shapes were shown on the patterned substrates. Patterned substrates exhibit anisotropic wetting as different contact angles are measured along the 0° and 45° lines of sight. Moreover, the addition of aluminum oxide and titanium oxide coatings made the substrates more hydrophilic, resulting in decreased initial droplet contact angles for the smooth and pillar patterned substrates. The increased hydrophilicity resulted in the droplets not exhibiting CCA mode on the pillar patterned substrate with aluminum oxide and titanium oxide coatings. The droplets also experience contact line pinning-depinning during the CCA and mixed modes on patterned substrates. The potential application of research within this area can be applied to liquid printing technology and microfluidic devices which require the understanding of droplet behavior on a minute scale. Besides, this research opens for more investigations into droplet wetting and evaporation behavior on substrates with micropillars, particularly on controlling the behavior through variation of substrate and coating properties.